Identification and Functional Analysis of the First Aquaporin from Striped Stem Borer, Chilo suppressalis - Lu, Ming-Xing; Pan, Dan-Dan; Xu, Jing; Liu, Yang; Wang, Gui-Rong; Du, Yu-Zhou (Frontiers in Physiology, 2018)
Aquaporins are integral membrane proteins some of which form high capacity water-selective channels, promoting water permeation across cell membranes. In this study, we isolated the aquaporin transcript (CsDrip1) of Chilo suppressalis, one of the important rice pests. CsDrip1 included two variants, CsDrip1_v1 and CsDrip1_v2. Although CsDrip1_v2 sequence (>409 bp) was longer than CsDrip1_v1, they possessed the same open reading frame (ORF). Protein structure and topology of CsDrip1 was analyzed using a predicted model, and the results demonstrated the conserved properties of insect water-specific aquaporins, including 6 transmembrane domains, 2 NPA motifs, ar/R constriction region (Phe69, His194, Ser203 and Arg209) and the C-terminal peptide sequence ending in “SYDF”. Our data revealed that the Xenopus oocytes expressing CsDrip1 indicated CsDrip1 could transport water instead of glycerol, trehalose and urea. Further, the transcript of CsDrip1 expressed ubiquitously but differentially in different tissues or organs and developmental stages of C. suppressalis. CsDrip1 mRNA exhibited the highest level of expression within hindgut and the third instar larvae. Regardless of pupae and adults, there were significantly different expression levels of CsDrip1 gene between male and female. Different from at low temperature, the transcript of CsDrip1 in larvae exposed to high temperature was increased significantly. Moreover, the mRNA levels of CsDrip1 in the third instar larvae, the fifth instar larvae, pupae (male and female), and adults (male and female) under different humidities were investigated. However, the mRNA levels of CsDrip1 of only female and male adults were changed remarkably. In conclusions, CsDrip1 plays important roles in maintaining water homeostasis in this important rice pest.